Identifikasi Kondisi Pohon Peneduh Terhadap Keselamatan Manusia Menggunakan Logika Fuzzy Mamdani - Fadhilah, Indra Malik Akbar (JISA(Jurnal Informatika dan Sains), 2018)
The condition of shade trees is very important for the safety of road users. It often happens in shade trees because of the factors of temperature, climate, air damage, and lack of oxygen in the tree. The purpose of this study is to study the health conditions in shady trees against human safety. So to overcome the problem in this study, a selective felling program in shady trees will bemade using the fuzzy logic method to solve the problem of existing factors by creating variables that will be used in processing on fuzzy logic. The results of this study are to identify which health conditions of trees that are feasible to be cut according to the results of fuzzy logic.